2016
DOI: 10.18632/oncotarget.7203
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA LINC00857 is predictive of poor patient survival and promotes tumor progression via cell cycle regulation in lung cancer

Abstract: We employed next generation RNA sequencing analysis to reveal dysregulated long non-coding RNAs (lncRNAs) in lung cancer utilizing 461 lung adenocarcinomas (LUAD) and 156 normal lung tissues from 3 separate institutions. We identified 281 lncRNAs with significant differential-expression between LUAD and normal lung tissue. LINC00857, a top deregulated lncRNAs, was overexpressed in tumors and significantly associated with poor survival in LUAD. knockdown of LINC00857 with siRNAs decreased tumor cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 52 publications
7
85
0
Order By: Relevance
“…16 LINC00857 predicts poor patient survival and it can promote tumor progression via regulating cell cycle in lung cancer. 17 In our current study, we found that LINC00857 was greatly increased in HCC cells. Knockdown of LINC00857 was able to inhibit HCC cell proliferation, induced cell apoptosis, and blocked cell cycle progression.…”
Section: Discussionsupporting
confidence: 52%
“…16 LINC00857 predicts poor patient survival and it can promote tumor progression via regulating cell cycle in lung cancer. 17 In our current study, we found that LINC00857 was greatly increased in HCC cells. Knockdown of LINC00857 was able to inhibit HCC cell proliferation, induced cell apoptosis, and blocked cell cycle progression.…”
Section: Discussionsupporting
confidence: 52%
“…AOC4P , also known as UPAT , was needed for the survival and tumorigenicity of colorectal cancer cells through regulating protein ubiquitination and degradation 41, and could also inhibit epithelial-mesenchymal transition in hepatocellular carcinoma 42. LINC00857 , which was upregulated in lung cancer, was predictive of poor patient survival and promoted tumor progression via cell cycle regulation 43. The functional and mechanistic aspects of these aberrantly expressed lncRNAs in gastric cancer need further in-depth investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 154 and 225 lncRNAs that are significantly associated with the response to Gem/Cis or platinum only treatment, respectively (Table ). Previously, LINC00857 was identified as one of the most upregulated lncRNAs in lung cancer, and high LINC00857 expression was associated with shorter overall survival of patients with lung cancer . Therefore, we decided to further focus on LINC00857 .…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate how LINC00857 contributes to platinum‐based chemotherapy response in bladder cancer, we evaluated the expression levels of LINC00857 target genes that were identified in lung cancer . In MIBC, the expression of DIAPH3 , EMR2 , MMP1 , STX12 , and UHMK1 was found to be significantly associated with response to Gem/Cis (Figure A) and other platinum‐based chemotherapy (Figure B).…”
Section: Resultsmentioning
confidence: 99%